EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) AND CARCINOEMBRYONIC ANTIGEN (CEA) RELATIONSHIP OF LUNG ADENOKARSINOMA IN SAIFUL ANWAR HOSPITA MALANG - Normawati Normawati; Suryanti Dwi Pratiwi; Nanik Setijowati (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: EGFR mutations is associated with sensitivity to tyrosine kinase inhibitors (TKI’s) therapy which are found in Lung Adenocarcinoma. There are some limitations in detecting EGFR mutation. CEA is also expected to predict treatment efficiency of EGFR-TKI's therapy. In this study, we investigated the relationship between serum Carcinoembryonic antigen (CEA) and Epidermal Growth Factor Receptor (EGFR) Mutations in Lung Adenocarcinoma patient. Methods : The research was conducted in Dr. Saiful Anwar General Hospital Malang. From May 2014 to November 2015, 54 lung adenocarcinoma patients who had underwent measurements of EGFR mutation and serum CEA level were retrospectively recruited. None of them had surgery, radiotherapy, chemotherapy and targeted therapy. EGFR mutation was detected using PCR, serum CEA levels were analyzed using electrochemical luminescence. Result: Abnormal serum levels of CEA were significantly associated with EGFR mutation (95% CI, P=0,043) with an odds ratio of 3.4 (95% CI: 1.010-11.451). The area under the ROC curve for CEA was 0.558 (95% CI, P=0.078). Conclusion: Serum CEA is associated with mutation of EGFR in lung adenocarcinoma patients. Keywords : Lung cancer, adenocarcinoma, EGFR, CEA